Contact Stresses between Two Cylindrical Bodies – Cylinder and Cylindrical Cavity with Parallel Axes – Part II: 2D and 3D FEA Comparative Study. (2015) - Brezeanu, Ligia Cristina
Abstract: This paper presents the results of a study carried out using the Finite Element Method, on the contact stresses between two bodies: cylindrical body in a cylindrical cavity. The results are compared, following the analysis, to the results calculated on basis of the relations in H. Hertz's theory. The analyzed situation is: cylindrical body of radius R1 in a cylindrical cavity of radius R2, both bodies having parallel axes. Considering the cylinder - cylindrical cavity assembly presents identical cross sections along the cylinder axis, both from the geometrical and loading point of view, this part of the paper models the problem with 2D elements using the plane strain formulation. The results are compared to the ones obtained on the spatial model and presented in the first part of the paper.